Cirebon Students' Cultural Shock In Adaptation To Lectures In Germany - Isma Qonaah; Komalasari Komalasari; Siti Khumayah; Farida Nurfalah (International Journal Labs, 2024)
Germany is one of the destinations for prospective students aiming to continue their higher education. This study aims to understand how Cirebon students adapt to academic activities and the challenges they face while studying in Germany. The research uses a qualitative method with a descriptive approach. Data collection techniques include in-depth interviews, observations, and a review of relevant previous research articles and related documents. The study employs intercultural communication theory, which covers aspects such as culture shock and adaptation phases to a new culture. The results show the stages that Cirebon students go through when adapting to a new culture: the honeymoon phase, characterized by initial excitement and enthusiasm about the new culture; followed by the frustration phase due to experiencing culture shock when facing the new culture. The next phase is readjustment, where students begin to understand and start learning about the new culture in their living environment and campus. The final phase is resolution, where Cirebon students accept the new culture in Germany. Before adaptation occurs, the study highlights challenges faced during academic activities in Germany, which are caused by internal factors such as religion, food, and weather.